Hungary without Capital Punishment: The Issue of the Deterrent Effect in Light of Criminal Statistics (1975-2024) - Toth J., Zoltan (PRAWO i WIĘŹ, 2025)
One of the most important issues related to the death penalty is whether it has a deterrent effect and can prevent potential perpetrators, primarily potential murderers, from committing crimes. However, positions expressed in the related theoretical debate must first of all be based on practical experience, especially statistical analyses that can provide probabilistic arguments for the strength of the deterrent effect theory. This study examines the homicide trend in Hungary over the past 50 years and concludes that, although the presence or absence of a deterrent effect cannot be precisely determined in theory, practical experience suggests that it plays a negligible role in the perpetrators’ motivation.